WO3 Photocatalyst Containing Copper Inactivates SARS-CoV-2 Pango Lineage A and Omicron BA.2 Variant in Visible Light and in Darkness - Matsuura, Ryosuke; Maeda, Ken; Hagiwara, Kyoji; Mori, Yosuke; Kitamura, Toru; Matsumoto, Yasunobu; Aida, Yoko (Pathogens (Basel), 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of coronavirus disease 2019, which has been a global pandemic. Since SARS-CoV-2 is transmitted through contaminated surfaces and aerosols, environmental disinfection is important to block the spread of the virus. Photocatalysts are attractive tools for virus inactivation and are widely used as air purifiers and coating materials. However, photocatalysts are inactive in the dark, and some of them need to be excited with light of a specific wavelength. Therefore, photocatalysts that can effectively inactivate SARS-CoV-2 in indoor environments are needed. Here, we show that a WO3 photocatalyst containing copper inactivated the SARS-CoV-2 WK-521 strain (Pango lineage A) upon irradiation with white light in a time- and concentration-dependent manner. Additionally, this photocatalyst also inactivated SARS-CoV-2 in dark conditions due to the antiviral effect of copper. Furthermore, this photocatalyst inactivated not only the WK-521 strain but also the Omicron variant BA.2. These results indicate that the WO3 photocatalyst containing copper can inactivate indoor SARS-CoV-2 regardless of the variant, in visible light or darkness, making it an effective tool for controlling the spread of SARS-CoV-2.